Evolusi Identitas Profesional dari Mahasiswa Menjadi Guru: Sintesis Penelitian Kualitatif - Diva Indah Maria Pandiangan; Mella Senteria Manalu; Desry Sapta Aglesi Tarigan; Nauli Hosianna Napitu; Romaito Ambarita; Risda Muliana Br. Pane; Mora Irani Gultom; Stevany Banjarnahor; Leonita Maria Efipanias Manihuruk (Yayasan Bayt Shufiya Nusantara, 2026)
Teaching practicum is a crucial phase in the formation of teacher identity, yet its evolutionary process is often complex and fraught with tension. This study aims to synthesize qualitative literature on how pre-service teachers' professional identity evolves during their practicum. Using a systematic literature review design with the PRISMA protocol, 26 articles (20 qualitative studies and 6 review articles) were collected from various geographical contexts. The synthesis results show that identity evolution moves from an idealistic imaginary identity phase to a phase of negotiating tensions between authority, theory, and practice. The final stage of the practicum reveals an integrated identity reconstruction, characterized by increased teacher self-efficacy and the development of a personal pedagogical style. This study concludes that mentor support and critical reflection are the primary catalysts determining the success of identity transformation. The implications of this research emphasize the need for a more intentional practicum design in supporting the emotional and discursive aspects of pre-service teachers.